THE RELATION OF ANXIETY AND KNOWLEDGE WITH LABOR READINESS IN COVID-19 PANDEMIC - Ervina Puspa Wahyu Angesti; Nining Febriyana (UNIVERSITAS AIRLANGGA, 2021)
Background: 107,000 pregnant women in Indonesia experiencing anxiety while facing childbirth. A Research shows that anxiety is more experienced in Primigravida's pregnant women. Pregnant women anxiety can arise, especially in the third trimester until delivery. During the COVID-19 pandemic, pregnant women feel increasingly anxious because the virus spreads relatively easily. This study was aimed to analyze the relationship between the anxiety level and knowledge of pregnant women in the third trimester with readiness to face childbirth during the COVID-19 pandemic in Puskesmas Benowo and Tenggilis. Methods: This type of research was observational analytic with a cross-sectional design. The number of samples was 76 third trimester pregnant women suitable the criteria that is primigravida, physiologic pregnancy, not in a long-term medication and willing to be a respondent. The sampling technique was purposive sampling. The data was analyzed with Spearman’s Statistic test. Results: as many as 57.5% of respondents had severe anxiety with low readiness for childbirth and good knowledge of COVID-19. It was caused by the drug or vaccine for the Covid-19 that had not been found, and made pregnant women even more anxious and feared of something unwanted happening. Anxiety of pregnant women who were about to give birth greatly affected the readiness of the mother in preparing for childbirth, the more anxious pregnant women were, the less they would be prepared for laboring. The statistic analyze says that There was a relationship between the level of anxiety of third trimester pregnant women with readiness to give birth during the COVID-19 pandemic (p = 0.00), there was a relationship between the knowledge level with readiness to give birthd during the COVID-19 pandemic p = 0.012). Conclusion: There is a relationship between the Anxiety Level and Knowledge of Pregnant Women in the third trimester with Readiness for Childbirth during the COVID-19 Pandemic